Análisis del tratamiento de noticias violentas publicadas en el diario digital ND noticias, Babahoyo 2021 - Amanta Fuentes, Paulina Liseth (2022)
This study is developed with the objective of analyzing the treatment of violent news published in the digital newspaper “ND Noticias” of the city of Babahoyo in the period 2021; in order to determine each of the procedures that are carried out prior to the publication of an informative note of this type, as well as to know the influence and scope it has on the target audience through social networks. Through the research line of the career "Information and Communication Technologies in the Network Society" and the subline "Journalistic Writing, genres, and digital narratives". In addition to the help of the analytical method that collects information on the processes that are carried out to generate notes of violent content in the digital medium, the same that is known through the application of the technique, a survey carried out on its administrator and owner, which originated as The result does not have a specific scheme structured for the treatment of violent news, except for specifications to protect the identity of the victims or relatives, on the other hand, it applies the same strategies, that is, the same type of content in both social networks where there is Instagram and Facebook, despite the fact that each one has policies and a different target audience, however, updates are made once a month, therefore, it does not have a considerable reaction or reach of people.